Implementasi Nilai Multikultural untuk Meningkatkan Kemampuan Berpikir Kritis Abad 21 pada Mata Kuliah Pendidikan Karakter - Faidin, Faidin; Suharti, Suharti (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2023)
Abstract: The aim of the research is to identify multicultural values to Improve Critical Thinking Skills and Respond to the Challenges of the 21st Century in Character Education Courses. This research was conducted at STKIP Harapan Bima using a qualitative approach with descriptive and literature review. The multicultural values instilled are the values of tolerance, democratic values, mutual respect and respect, and the values of cooperation. Meanwhile, the values that are part of answering the 21st century are open, fair, flexible and honest. The inculcation of multicultural values at STKIP Harapan Bima is a manifestation of values in 21st century life, on the basis of these values the ability to think critically can be improved. The realization of instilling multicultural values is carried out through classroom learning in character education courses to strengthen the multicultural character of students.